Kinetic Parameter Studies Of Activated Sludge Process For Anaerobic Pre-Treated Palm Oil Mill Effluent - Che Ibrahim, Ahmad Kamarulnajuib (2007)
A study on the evaluation of kinetic parameters for activated sludge process treating palm oil mill effluents is reported. It is hypothesized that kinetic parameters are applicable for analyzing the performance of activated sludge process for treating high strength palm oil mill effluents (POME). The kinetic parameters were obtained through bench-scale continuous flow experimental studies and batch studies using respirometry technique. The studies utilized samples of POME obtained from a facultative pond from an existing palm oil mill. The bench scale studies were conducted by treating the POME in three modes: first, the sample POME was mixed with activated carbon; second, the sample as a perforated plastic as a medium was submerged in the sample and third, the sample was used as is without being mixed with the activated carbon or any medium. The activated carbon was made from palm kernel and was prepared as well as characterized in the laboratory.